ANALISIS PENGARUH PELATIHAN TERHADAP PENINGKATAN KEMAMPUAN PNS DI BALAI PU WILAYAH-I MEDAN - Putri Yulia; Harmein Nasution; Iskandarini Iskandarini (Studia Economica : Jurnal Ekonomi Islam, 2015)
Training is a process of learning to develop the patterns of people behavior in science, skills or attitudes to achieve the expected standards. The aim in this study is to determine the training effect of civil servants in the Central Region I Field PU. The result of Adjusted R Square is 0.613 which means the independent variables can be explained by the variability of the dependent variable about 61.3%, or in other words the ability of independent variables, namely knowledge, skills, motivation, curriculum/materials, teacher, facilities and learning methods describes the influence of training to the civil servants at the Public Hall Area I about 61.3%. Independent variables that are knowledge, skills, motivation, curriculum/materials, teacher, facility this gives meaning if the knowledge, skills, motivation, curriculum/materials, teacher, facilities and learning methods are increased simultaneuosly, they will have an impact on upgrading PNS. Test showed that knowledge significant effected significantly on increasing the capability of civil servants, Expertise effected significantly on increasing the capability of civil servants, motivation and curriculum/material did not effect on increasing the capability of civil servants, teacher effected significantly on increasing the capability of civil servants, Facilities, learning methods are effected significantly on increasing the capability of civil servants